LEMON AROMATHERAPY AS AN ALTERNATIVE TO REDUCE THE INTENSITY OF CHEMOTHERAPY-RELATED NAUSEA AND VOMITING EXPERIENCED BY THE BREAST CANCER PATIENTS - Puji Hastuti; Yuli Nurhayati; Dwi Ernawati; Christina Yuliastuti; Merina Widyastuti (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2021)
ABSTRACT Introduction : The mechanism of breast cancer is the cells growing and breeding become appear abnormal tissue of breast. One of the common treatments for it is chemotherapy using cytotoxic drugs. However, chemotherapy may cause nausea and vomiting as its side effects. Lemon aromatherapy is a complementary therapy in patients with breast cancer who experience nausea or vomiting. The study’s purpose was to know the effect of lemon aromatherapy on the intensity of nausea and vomiting experienced by the breast cancer patients as an effect of chemoterapy in the Chemo Center Room of RSAL Dr. Ramelan Surabaya. Material and Methods : The study was the pre-experimental design with pre-post test without control group. There are two variables, lemon aromatherapy is independent, and the intensity of nausea and vomiting is dependent. The sampling technique was nonprobability purposive sampling, with 34 breast cancer patients taken as the sample. A questionnaire was the instrument for collecting the data. The Data collected were analyzed using the Wilcoxon Test (α = 0,05). Results : The study’s result indicated that the lemon aromatherapy was effectively to decrease of the intensity of nausea and vomiting exeperienced by the respondents, with the value of Wilcoxon test p < 0.001. Conclusion : Lemon aromatherapy stimulates the raphe nucleus to produce serotonin. Which function to generate a sense of comfort and calm. For that reason, it can be used as an alternative for taking care of nausea and vomiting experienced by patients with breast cancer as the side effect of chemotherapy. Keywords: Lemon Aromatherapy, Nausea, Vomiting, Chemotherapy